Intensity of crossbridge heirfers under different technologies content - Рубан, С. Ю.; Борщ, О. О. (Scientific Progress & Innovations, 2017)
The use of cross-breeding as an element of improving livestock in commercial herds affected the growth and development of first-generation heifers compared to pure-blooded counterparts. The heifers of the Ukrainian black-rye dairy breed were characterized by higher live weight values ​​compared to the Brown Swiss, while the heifers were obtained as a result of the crossing of the Monbeliarde breed with the Ukrainian red-rye milk breed; on the contrary, they were marked by a larger live weight than the red-rye ones. According to the indices that characterize the intensity of their growth and development, the heifers of Ukrainian black-rye milk breed had higher rates in all indices compared with their respective counterparts. In studies conducted on heifers of the Ukrainian red-rye dairy and Monbeliarde breeds, it was established that they were dominated by red-rye analogues by indicators of growth.